Pediatrician’s role on patients with learning disabilities: a pilot study - Vanessa Pacini Inaba Fernandes (Revista Paulista de Pediatria)
ABSTRACT Objective: Learning disability leads to school dropout and low self-esteem in childhood, low socioeconomic status, increased criminality, and incarceration in adulthood. Pediatricians are key professionals who can diagnose and prevent this. The objective of the study was the early detection and reference of children with learning disabilities as identified by their schoolteachers. Methods: The protocol included: specific anamnesis with parents; Snellen test; audiometry and central auditory processing test; referral to speech therapists, ophthalmologists, otorhinolaryngologists, psychiatrists, psychologists, and neurologists if necessary; validated screening tests to evaluate literacy and mathematics reasoning skills; and development of a report for parents and teachers on the suspected diagnosis, professional referral, and curricular adjustments. Results: A total of 15 patients were evaluated in 1 year, with a mean age of 10.3 years, median school fourth grade, and mostly males (80%). The time for final report delivery was 6.4 months. Visual impairment was identified in 35.7% and central auditory processing impairment in 100% of patients. For writing and reading skills, seven children had below average and two children had average scores; for mathematics skills, five had below average, one average, and one higher score. Six children were illiterate and were suspected of having autism spectrum disorder, attention-deficit hyperactivity disorder, oppositional defiant disorder, intelligence disability, or borderline intelligence coefficient. Conclusions: A specific protocol helped to identify sensory organ impairments and psychological and psychiatric conditions, quantify school hardship, and provide a report with a suspected diagnosis and referral for treatment of learning disabilities. Larger population studies and a control group are necessary to validate this protocol.